After one hundred years : the 1910 exhibition "Meisterwerke muhammedanischer Kunst" reconsidered - Lermer, Andrea.; Shalem, Avinoam. (Islamic History and Civilization, 2010)
The exhibition \'Meisterwerke muhammedanischer Kunst\' that took place in Munich in 1910 marked a turning point in the approach to Islamic Art. The show attempted to break free of Orientalism and exotic fantasies and, in doing so, set a new standard for the reception of Islamic art in Europe. Moreover, naming the Islamic artefacts masterpieces, it layed claim to bestow upon Islamic art "a place equal to that of other cultural periods". This book is the first comprehensive study on this path-breaking exhibition. It includes a wealth of unpublished material and numerous novel ideas on the subject and addresses the exhibition's historical context, organization, realization and display as well as its reception in the West and its later influence on the study of Islamic art.